Case studies in abnormal child and adolescent psychology - Weis, Robert (Thousand Oaks, California : SAGE Publications, Inc., 2021)
Case Studies in Abnormal Child and Adolescent Psychology is designed to accompany the textbook Introduction to Abnormal Child and Adolescent Psychology by Robert Weis. Clinical case examples based on real children and parents pair with chapters in the core text to illustrate principles of developmental psychopathology, psychological assessment, evidence-based treatment, and examples of specifics disorders prevalent in children and adolescents.
PART I: CONCEPTS, METHODS, AND THEORIES -- Chapter 1: The Science and Practice of Abnormal Child Psychology -- Chapter 2: The Causes of Childhood Disorders -- Chapter 3: Research Methods with Children and Families -- Chapter 4: Assessing and Treating Children$1 (Bs Problems -- PART II: CASE STUDIES OF CHILDREN AND ADOLESCENTS -- Chapter 5: Intellectual Disability & Developmental Disorders -- Chapter 6: Autism Spectrum Disorder (ASD) -- Chapter 7: Communication & Learning Disorders -- Chapter 8: Attention-Deficit/Hyperactivity Disorder -- Chapter 9: Conduct Problems in Children and Adolescents -- Chapter 10: Substance Use Problems in Adolescents -- Chapter 11: Anxiety Disorders and Obsessive-Compulsive Disorder -- Chapter 12: Trauma-Related Disorders -- Chapter 13: Depression, Suicide, and Self-Injury -- Chapter 14: Paediatric Bipolar Disorders & Schizophrenia -- Chapter 15: Feeding & Eating Disorders -- Chapter 16: Health-Related Disorders & Pediatric Psychology.s
Keywords: ADOLESCENT; ADOLESCENT PSYCHOPATOLOGY